ANALYSIS OF INTERNATIONAL CARGO TURNOVER AND CO2 EMITTED DURING ITS ORGANIZATION (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article presents an analysis of international freight turnover and the associated CO2 emissions. It examines the key aspects affecting the efficiency and environmental consequences of freight transport, including transport routes, modes of transport and their impact on the carbon footprint.